Pelatihan Pembelajaran Sains dengan Pendekatan Investigative Science Learning Environment (ISLE) bagi Guru Sekolah Dasar di SD Yohannes Gabriel Surabaya - Pratidhina, Elisabeth; Herwinarso, Herwinarso; Palupi, Retno; Tamah, Siti Mina; Wibowo, Endra Putra; Marcelinda, Caroline (Jurnal Abdi Masyarakat Indonesia, 2025)
Science education in primary schools has an important role in fostering scientific attitudes and environmental literacy. This community service program aims to improve the quality of science learning in elementary schools through the application of the Investigative Science Learning Environment (ISLE) approach integrated with environmental literacy. The activities were carried out at Yohannes Gabriel Elementary School in Surabaya through several stages: preparation, socialization, training, implementation assistance, and evaluation. There were 10 teachers participating in this training. Teachers were trained to understand the concept of ISLE, to integrate environmental issues into science learning, and to design contextual and engaging teaching media. The evaluation results after the training showed an increase in teachers’ understanding of the ISLE approach with an N-gain score of 0.75. Once teachers understand ISLE, they will be able to develop active learning and apply it to their students. This collaboration also strengthens the partnership between higher education institutions and elementary schools in developing pedagogical innovations relevant to the challenges of 21st-century education.